Penerapan Model Discovery Learning Dalam Meningkatkan Kemampuan Berpikir Kritis siswa Pada Pembelajaran Pendidikan Pancasila Kelas V SD - Janfira, Vika; Muhisom; Kembar Habibi, Roy; Nurwahidin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low critical thinking ability in the Pancasila Education subject of fifth-grade students of SD. This study aims to determine the effect of the discovery learning model on students' critical thinking abilities. The research method used is a quasi-experimental design with a nonequivalent control group design. The sampling technique used purposive sampling, with a population of 78 students and a sample of 52 students. Data collection techniques used tests and non-tests in the form of observation sheets. Hypothesis testing used a simple linear regression test analysis with the results of Fcount > Ftable, namely 26.623> 4.26, and a significance value of 0.000 <0.05. Thus, it can be concluded that there is a significant influence of the use of the discovery learning model on students' critical thinking abilities in the Pancasila Education subject of fifth-grade students of SD.